Versatile and robust genome editing with Streptococcus thermophilus CRISPR1-Cas9 - Agudelo, Daniel; Carter, Sophie; Velimirovic, Minja; Duringer, Alexis; Rivest, Jean-François; Levesque, Sébastien; Loehr, Jeremy; Mouchiroud, Mathilde; Cyr, Denis; Waters, Paula J.; Laplante, Mathieu; Moineau, Sylvain; et al. (Genome Research, 2020)
Targeting definite genomic locations using CRISPR-Cas systems requires a set of enzymes with unique protospacer adjacent motif (PAM) compatibilities. To expand this repertoire, we engineered nucleases, cytosine base editors, and adenine base editors from the archetypal Streptococcus thermophilus CRISPR1-Cas9 (St1Cas9) system. We found that St1Cas9 strain variants enable targeting to five distinct A-rich PAMs and provide a structural basis for their specificities. The small size of this ortholog enables expression of the holoenzyme from a single adeno-associated viral vector for in vivo editing applications. Delivery of St1Cas9 to the neonatal liver efficiently rewired metabolic pathways, leading to phenotypic rescue in a mouse model of hereditary tyrosinemia. These robust enzymes expand and complement current editing platforms available for tailoring mammalian genomes.